What’s Love Got to Do With It? Team Entrepreneurial Passion and Performance in New Venture Teams - Santos, Susana C.; Cardon, Melissa S. (Entrepreneurship Theory and Practice, 2019)
We integrate literatures on entrepreneurial passion, shared emotions, and group identities to extend a conceptual model of team entrepreneurial passion (TEP). We delineate mono-focal, complete, and incomplete poly-focal TEP, and examine how each type and focus of TEP is related to team performance. We test our hypotheses with 73 new venture teams. Results reveal that TEP occurs in 61 teams in our sample (23 mono-focal, 26 complete poly-focal, 12 incomplete poly-focal). In terms of focus, TEP for inventing and developing are positively related to team performance. Concerning type, mono-focal and complete poly-focal TEP are the most beneficial for team performance.